I. Andrzejuk, A. Andrzejuk, Tomasz z Akwinu jako etyk, Wydawnictwo von borowiecky, Warszawa 2021, 171+1s., ISBN: 9788366480315 - Szymonik, Marian (Częstochowskie Studia Teologiczne, 2022)
Recenzja ksiązki: I. Andrzejuk, A. Andrzejuk, Tomasz z Akwinu jako etyk, Wydawnictwo von borowiecky, Warszawa 2021, 171+1s., ISBN: 9788366480315